EFEKTIVITAS EKSTRAK KULIT BATANG Rhizophora mucronata SEBAGAI ANTIBAKTERI UNTUK MENCEGAH PERKEMBANGAN BAKTERI Edwardsiella tarda PADA IKAN MAS (Cyprinus carpio L.) - Ainul Mardiah; Dwi Suryanto; Desrita Desrita (AQUACOASTMARINE, 2016)
This study was aimed to determine antimicrobial potential of stembark extract of R. mucronata against bacterial pathogens E. tarda, to know the extract toxicity to gold fish (Cyprinus carpio. L), and to know the effect of the extract to fish survival rate. Antimicrobial assay of the extract was done using diffusion method, LC50 assay was conducted by putting the fish into chamber with extract concentration of 0, 25, 30, 50, and 75 ppm in water. Survivalship assay to the methanol extract was conducted at concentration of 2,86 and 3,93 ppm along with E. tarda inoculation. To examine stembark extract in inhibition disease caused by E. tarda, methanol extract of the stembark was used in this examination. Goldfish of 5 - 7 cm were subjected to be infected with E. tarda of 107 CFU/ml in intraperitoneal. The result showed that the methanol extract of the stembark was more effective in inhibiting grow of E. tarda. LC50 of the methanol extract was in 39,30 ppm. The methanol extract of 3,93 ppm showed to reduce E. tarda cell from 2,18 x 103 CFU/ml to 1,32 x 103 CFU/ml in gold fish. It showed that methanol extract of 3,93 ppm were not toxic to the fish shown by survival rate of 100%. Survival rate of goldfish treated with the methanol extract was high compared to that of E. tarda ((-) control). The soaking of stembark extract showed a significant effect (P<0.05) toward survival rate of goldfish infected by E. tarda.Keywords : Antibacteria activity, Edwardsiella tarda, Rhizophora mucronata, challenge test